2022
DOI: 10.5713/ab.21.0462
|View full text |Cite
|
Sign up to set email alerts
|

Feeding broiler chicks with Schizosaccharomyces pombe-expressed phytase-containing diet improves growth performance, phosphorus digestibility, toe ash, and footpad lesions

Abstract: Objective: The objective of this study was to evaluate the effects of dietary supplementation of Schizosaccharomyces pombe (S. pombe) -expressed phytase on growth performance, apparent ileal digestibility, organ indexes, meat quality, toe ash, and footpad lesions score in broiler chicks.Methods: A total of 390 one-day-old broiler chicks were randomly assigned to 5 groups based on the initial body weight (42.15±0.17 g), there were 6 replicate cages per treatment and 13 birds (mixed sex) per cage. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Even pathological, poor husbandry practice, and diet may affect footpad infection in broilers. In the current study, there was no sign of diarrhea (Figure 1) which in turn causes footpad dermatitis (Figure 2), and we supposed that the healthy foot pad condition of the broilers could be due to the effect of dietary phytase, which enhanced nutrient utilization by breaking down phytic acid, leading to improved digestion that resulted with reduced wet litters [35] or due to proper sanitary conditions. et al [31] reported that the changes in poultry foot pads are related to the housing sys-tem, particularly hyperplasia occurs due to mechanical stimulation when perches and hens are used in the litter and is also observed as an alteration with cage-reared hens' toe and claw regions.…”
Section: Resultsmentioning
confidence: 59%
“…Even pathological, poor husbandry practice, and diet may affect footpad infection in broilers. In the current study, there was no sign of diarrhea (Figure 1) which in turn causes footpad dermatitis (Figure 2), and we supposed that the healthy foot pad condition of the broilers could be due to the effect of dietary phytase, which enhanced nutrient utilization by breaking down phytic acid, leading to improved digestion that resulted with reduced wet litters [35] or due to proper sanitary conditions. et al [31] reported that the changes in poultry foot pads are related to the housing sys-tem, particularly hyperplasia occurs due to mechanical stimulation when perches and hens are used in the litter and is also observed as an alteration with cage-reared hens' toe and claw regions.…”
Section: Resultsmentioning
confidence: 59%
“…However, information on the health effects of S. pombe in pigs is limited. In turn, supplementation with S. pombe has been shown to improve nutrient uptake and growth performance in broiler chickens [54].…”
Section: Discussionmentioning
confidence: 99%